EFEKTIFITAS TERAPI BEKAM DAN TERAPI AKUPUNTUR TERHADAP PENURUNAN KADAR KOLESTEROL DI DESA CONDONG KECAMATAN GADING KABUPATEN PROBOLINGGO - Nur Aulia Utami; Alwin Widhiyanto; Nur Hamim (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Cholesterol is the most important amphylactic layer in regulating membrane permeability and fluidity, and is also the outer layer of plasma lipoproteins. This research aims to determine whether cupping therapy and acupuncture therapy are more effective in Condong Village, Gading District, Probolinggo Regency. This type of research is pre-experimental with a two group pre-post design. The population of all elderly people suffering from cholesterol in Condong Village, Gading District, Probolinggo Regency was 60 respondents. The sample was determined using a random sampling technique which met the criteria of 36 respondents. The instruments used are cupping tools and acupuncture tools as well as aesy touch. Data processing using Editing, Coding, Scoring and Tabulating processes, then analyzed using the paired t test. The results of this study show the average value of reduction in cholesterol levels that occurs after cupping therapy and acupuncture therapy. in cholesterol sufferers for pre-post cupping it was 6.05 while the acupuncture therapy intervention was worth 3.65. analysis test results using the paired t test. Cupping therapy is more effective than acupuncture therapy for cholesterol sufferers in Condong Village, Gading District, Probolinggo Regency, ( -valeu = 0.000 < α = 0.05). Cupping therapy and acupuncture therapy are effective therapies for lowering cholesterol levels and is recommended especially for people with cholesterol levels